Alcohol intake and stomach cancer risk in Japan: A pooled analysis of six cohort studies. Issue 1 (28th November 2021) - Tamura, Takashi; Wakai, Kenji; Lin, Yingsong; Tamakoshi, Akiko; Utada, Mai; Ozasa, Kotaro; Sugawara, Yumi; Tsuji, Ichiro; Ono, Ayami; Sawada, Norie; Tsugane, Shoichiro; Ito, Hidemi; et al.
Abstract: The association between alcohol intake and stomach cancer risk remains controversial. We undertook a pooled analysis of data from six large‐scale Japanese cohort studies with 256 478 participants on this topic. Alcohol intake as ethanol was estimated using a validated questionnaire. The participants were followed for incidence of stomach cancer. We calculated study‐specific hazard ratios (HRs) and 95% confidence intervals (CIs) for stomach cancer according to alcohol intake using a Cox regression model. Summary HRs were estimated by pooling the study‐specific HRs using a random‐effects model. During 4 265 551 person‐years of follow‐up, 8586 stomach cancer cases were identified. In men, the multivariate‐adjusted HRs (95% CIs) of stomach cancer were 1.00 (0.87‐1.15) for occasional drinkers, and 1.00 (0.91‐1.11) for <23 g/d, 1.09 (1.01‐1.18) for 23 to <46 g/d, 1.18 (1.09‐1.29) for 46 to <69 g/d, 1.21 (1.05‐1.39) for 69 to <92 g/d, and 1.29 (1.11‐1.51) for ≥92 g/d ethanol in regular drinkers compared with nondrinkers. In women, the multivariate‐adjusted HRs were 0.93 (0.80‐1.08) for occasional drinkers, and 0.85 (0.74‐0.99) for <23 g/d, and 1.22 (0.98‐1.53) for ≥23 g/d in regular drinkers compared with nondrinkers. The HRs for proximal and distal cancer in drinkers vs nondrinkers were 1.69 (1.15‐2.47) and 1.24 (0.99‐1.55) for ≥92 g/d in men, and 1.60 (0.76‐3.37) and 1.18 (0.88‐1.57) for ≥23 g/d in women, respectively. Alcohol intake increased stomach cancer risk in men, and heavy drinkers showed a greater point estimate of risk for proximal cancer than for distal cancer. Abstract : Alcohol intake increased stomach cancer risk in men, and heavy drinkers showed a greater point estimate of risk for proximal cancer than for distal cancer.